As mudanças ocorridas no livro didático de matemática e a sua influência na prática pedagógica do professor - Turíbio, Solange Ramos Teixeira (2015)
This paper aims to comprehend teachers’ practices through in-class textbook use, since this is an important supportive tool for the teaching task. The investigations carried out following such perspective made it possible to verify the existence of a considerable theoretical background regarding the theme - Mathematics and Geometry Teaching - yet, regarding the role of the textbook effect on teacher’s practice, there is not much bibliography available. The aim of this research was to investigate the level of influence on the Mathematics textbook syllabus organization considering the pedagogical practice of the professionals who teach Mathematics to senior students in Board School. This very paper was intended to answer the following questions: a) how is Mathematics taught at school? b) do the teachers make use of a textbook to teach? c) how do they use it? d) if they use it, how is the selecting process of the Mathematics textbook like? e) does the content organization expressed in the textbook influence the teacher’s pedagogical practice? In order to achieve its goal, it initially follows the reflections on the importance of the textbook in the schooling context by Soares (1996), Lajolo (1996), Choppin (2004), Bittencourt (2004) and Carvalho e Lima (2010). Regarding the ponderings about Mathematics itself as well as its teaching, such study followed the ideas by D’Ambrósio (1993), Gadotti (1995), Fiorentini (1995, 2002), Polya (1997), Gáscon (1998), Dante (1998), Pais (2002), Onuchic (2004), D’Ambrósio (1990, 2012), Silva (2009), Cavalcanti (2010) and Freire (2013). The considerations about teaching Geometry were based on Dana (1994), Grande (1994), Usiskin (1994), Vitti (1994) and Nacarato (2002). Theoretical fundaments of qualitative research are also at use, relying on data collecting tools, observation, interview and document analysis. In order to verify changes that occurred in the way of organizing such contents in textbooks selected for the research, content analysis was prime, and the interpretative method was employed to analyze the notes related to teachers’ practices in the classroom. The textbook analysis highlighted significant changes in relation to content presentation, mostly Geometry-related ones. However, it is possible to admit that, despite Geometry’s being part of several topics that were covered, studying-teaching Geometry is not a priority yet, since it continues to be placed at the end of the textbook, as its last chapters. During the observation period, it was also possible to realize that, despite the teacher’s knowledge as well as his/her autonomy to select themes s/he considered necessary through his/her students’ life, there are moments when s/he needs to rely on the textbook itself. The investigation we focus on here does not intend to propose new methodologies or solutions to the problems involving the inadequate use of the textbook in the classroom, rather it is a way to provide questions that may lead to reflection on the importance of such tool in the classroom environment.